Penta-helix collaboration, tourism development, and community welfare: A case study of Alas Kedaton, Tabanan - Sanjaya, Putu Krisna Adwitya; Budhi, Made Kembar Sri; Purbadharmaja, Ida Bagus Putu; Yasa, I Nyoman Mahaendra (Edelweiss Applied Science and Technology, 2025)
This study aims to analyze the influence of penta-helix elements and tourism development performance on community welfare at the Alas Kedaton Tourist Attraction in Kukuh Village, Tabanan. A mixed-method approach with an explanatory sequential design was employed, beginning with a survey of 148 residents from 12 traditional hamlets, followed by in-depth interviews and focus group discussions with 10 key stakeholders. Data analysis was conducted using a quantitative descriptive approach and Structural Equation Modeling with Partial Least Squares software. The findings reveal a significant influence of government, private sector, community, academic, and media roles on tourism development performance. The study also finds a significant influence of these five roles and tourism development performance on community welfare. Furthermore, tourism development performance is identified as a mediating variable in the relationship between penta-helix elements and community welfare. The practical implication of this research emphasizes the importance of synergy among penta-helix elements to enhance tourism development performance and improve community welfare. Therefore, it is essential for internal stakeholders to foster and strengthen penta-helix collaboration as a strategy to accelerate the recovery of the Alas Kedaton Tourist Attraction and achieve community prosperity.